Approach and avoidance alcohol inclinations in heavy drinking college students: An ecological momentary assessment study. (December 2021) - Gius, Becky K.; Schlauch, Robert C.
Highlights: Within- and between-person effects of craving and competing desires examined. Within-person changes in craving and competing desires predict alcohol use. Within-person avoidance inclinations attenuates the effect of approach on drinking. Results illustrate the importance of both approach and avoidance on daily drinking. Abstract: Background: Understanding the motivational determinants of drinking among college students is necessary to improve the identification of those at greatest risk and to inform prevention and treatment interventions. Alcohol craving, or the desire to use alcohol, is considered one important factor in the development and maintenance of drinking behaviors. Recent evidence suggests that the link between alcohol craving (approach inclinations) and alcohol use is moderated by desires not to use alcohol (avoidance inclinations). Using ecological momentary assessment, the present study investigated the influence of motivational conflict (high desires to use and high desires to not use alcohol) on alcohol consumption among college students. Methods: Undergraduate students (n = 80; 88.8% female) completed assessments of alcohol-related behaviors and alcohol motivation five times daily for fourteen days. Results: Although between-person effects were nonsignificant, significant within-person effects indicated that avoidance inclinations attenuated the effect of approach inclinations in the prediction of drinking (controlling for age, gender, drinking history, affect, day of week, and time of day). Conclusions: Findings highlight the need for consideration of the unique effects of both approach and avoidance inclinations in the prediction of alcohol consumption and draw attention to the need for further investigation into the complex interplay of these processes in daily life.